Standardisation of Protein S in Plasma: Calibration of the 1st International Standard - Hubbard, Anthony R (Thrombosis and Haemostasis, 1997)
An international collaborative study, involving 16 laboratories, was carried out to calibrate the 1st International Standard Protein S, plasma, for total and free Protein S antigen and for Protein S function. Potency estimates were calculated relative to locally collected fresh normal plasma pools. Estimates of total Protein S antigen showed good agreement between laboratories with inter-laboratory geometric coefficient of variation (gcv%) of 8.8% and a mean value of 0.89 IU/ampoule. Estimates of free Protein S antigen calculated relative to total Protein S antigen in the fresh normal pools were more variable (gcv 26.8%) than estimates calculated relative to free Protein S antigen (gcv 15.3%); the latter comparison was used for calibration with a mean value of 0.89 IU/ampoule. Functional Protein S was estimated using commercial kits which gave an overall mean value of 0.92 IU/ampoule (gcv 14.0%). The 1st International Standard Protein S, plasma, (coded 93/590) was established in October 1995 with a single potency of 0.90 IU/ampoule for all three parameters.